Affordances, complexities, and challenges of intercultural citizenship for foreign language teachers - Porto, Melina (2019)
This article explores the intercultural and citizenship dimensions of foreign language teaching and discusses, in particular, the implications for foreign language teaching and teacher education. The work extends the fundamental concepts that were developed by Byram and Wagner (2008) in this journal-that foreign language education has instrumental purposes but also educational aims that constitute the development of the individual and of societies by fostering democratic competences and values and linking the language learning that takes place in classrooms with the community, whether local, regional, or global; and links language education and community engagement in the form of service-learning, which was also addressed in this journal by Palpacuer Lee, Curtis, and Curran (2018). An intercultural citizenship project carried out in Argentina serves as illustration. Pedagogical implications are offered.